2017
DOI: 10.1021/acs.jpcc.7b00674
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Light Extraction from p-Si Nanowires/n-IGZO Heterojunction LED by Using Oxide–Metal–Oxide Structured Transparent Electrodes

Abstract: Heterojunction light-emitting diodes (LEDs) comprising p-type Si nanowires (p-Si NWs) and n-type indium gallium zinc oxide (n-IGZO) were fabricated with the different top electrode materials: Al, indium zinc oxide (IZO), and IZO/Ag/IZO oxide–metal–oxide (OMO) multilayer. All the LEDs exhibited typical rectifying behaviors of the p–n junction. Moreover, broad light-emission spectra in the visible range were observed because of the quantum confinement effect (QCE) of the Si NW and Si nanocrystals/nonstoichiometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…It is suggested that there is a non-radiative electron capture from the conduction band by a singly charged oxygen vacancy ( V o + ) due to the formation of unstable V O + state that recombines with a photoexcited hole in the valance band ( V o → VB), yielding green emission ( G CSD and G PLD ) of approximately 500–530 nm depending upon the formation energy of V o states . The origin of the yellow emission ( Y CSD and Y PLD ) is commonly attributed to the doubly charged oxygen vacancy ( V O ++ ) and also due to band transition from zinc interstitial (Zn i ) to oxygen interstitial (O i ). The red emission ( R CSD and R PLD ) can be attributed to the defect state of Si NWs and depends on the crystallinity of Si NWs and interface characteristics of p-Si NWs/ZnO heterostructures, and the integrated area of red emission is larger for the CSD-grown heterostructure shown in Table .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that there is a non-radiative electron capture from the conduction band by a singly charged oxygen vacancy ( V o + ) due to the formation of unstable V O + state that recombines with a photoexcited hole in the valance band ( V o → VB), yielding green emission ( G CSD and G PLD ) of approximately 500–530 nm depending upon the formation energy of V o states . The origin of the yellow emission ( Y CSD and Y PLD ) is commonly attributed to the doubly charged oxygen vacancy ( V O ++ ) and also due to band transition from zinc interstitial (Zn i ) to oxygen interstitial (O i ). The red emission ( R CSD and R PLD ) can be attributed to the defect state of Si NWs and depends on the crystallinity of Si NWs and interface characteristics of p-Si NWs/ZnO heterostructures, and the integrated area of red emission is larger for the CSD-grown heterostructure shown in Table .…”
Section: Results and Discussionmentioning
confidence: 99%
“…39 The origin of the yellow emission (Y CSD and Y PLD ) is commonly attributed to the doubly charged oxygen vacancy (V O ++ ) and also due to band transition from zinc interstitial (Zn i ) to oxygen interstitial (O i ). 32−34 The red emission (R CSD and R PLD ) can be attributed to the defect state of Si NWs and depends on the crystallinity of Si NWs and interface characteristics of p-Si NWs/ZnO heterostructures, 40 and the integrated area of red emission is larger for the CSD-grown heterostructure shown in Table 1.…”
Section: Investigation Of Defects In Xps and Plmentioning
confidence: 99%
“…Solar cell architecture of the 4-terminal based wide bandgap top cell (Si NWs) and narrow bandgap bottom cell for best matching efficiency with 10% Ge in SiGe active layer is possible, where the photocurrent limits under the solar spectrum for varying band gap of SiGe materials due to the Ge composition for bottom Heterojunction solar cell applications can be achieved [53]. Heterojunction light-emitting diodes (LEDs) comprising p-type Si nanowires (p-Si NWs) and n-type indium gallium zinc oxide (n-IGZO) were successfully fabricated [54]. Band gap energy of Si NWs can be controlled around 1.7 eV by changing the diameter of the NW [3].…”
Section: Figure 5 (A) High-resolution Cross-sectional Tem Image Around the Si-substrate And Deposited In-nds Surrounded By Simentioning
confidence: 99%
“…Progress in the field of using TCOs as both dopant and electrode layers for NW-LEDs is in a nascent stage and, only a few reports have been published. [31][32][33] In this work, we investigate the electrical and optical properties of SnO x layer deposited at different conditions and dem-onstrate that there is always a trade-off between high electrical conductivity and transparency. Subsequently, we investigate the performance of n-SnO x /p-InP NW LEDs, which can open up a myriad of applications of transparent electrode for LEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Progress in the field of using TCOs as both dopant and electrode layers for NW‐LEDs is in a nascent stage and, only a few reports have been published. [ 31–33 ]…”
Section: Introductionmentioning
confidence: 99%